Keterlibatan Multipihak Dalam Sistem Agribisnis Jeruk Pamelo Di Kabupaten Pangkep: Multistakeholder Involvement in Pomelo Citrus Agribusiness System in Pangkep Regency - Marhawati (Journal of Agriculture and Social Development, 2022)
Stakeholders have a very important role in managing pomelo citrus commodities. Thus, an understanding of the existence and role of multi-stakeholders is needed in realizing sustainable management of agricultural resources. This study aims to identify, categorize and investigate the relationship between stakeholders in the development of pomelo citrus agribusiness in Pangkep Regency. Data collection was carried out using the snowball sampling method and then analyzed descriptively and qualitatively. The results of the study show that there are three groups, namely primary, key, and secondary (supporting) stakeholders. Stakeholders as subjects are farmers, farmer groups, Gapoktan (group of farmer groups), pomelo orange farmer associations, and pomelo orange processing household industries. Stakeholders as key players, Department of Food Crops and Livestock, PPL (agricultural extension agency), Traders. Stakeholders as context setters for Bappeda Pangkep Regency, and stakeholders as crowds are sub-district heads, village heads, universities/research institutions. The relationship that occurs between stakeholders is a cooperative relationship, a complementary relationship, and a relationship that has the potential for conflict. Pemangku kepentingan (stakeholder) memiliki peranan yang sangat penting dalam implementasi pengelolaan komoditi jeruk pamelo. Dengan demikian, pemahaman akan keberadaan dan peranan multipihak diperlukan dalam mewujudkan pengelolaan sumberdaya pertanian yang berkelanjutan.  Penelitian ini bertujuan mengidentifikasi, membuat kategori dan menyelidiki hubungan antara pemangku kepentingan dalam pengembangan agribisnis jeruk pamelo di Kabupaten Pangkep.  Pengumpulan data dilakukan dengan metode snowball sampling untuk kemudian dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa terdapat tiga kelompok yaitu stakeholder primer, kunci dan sekunder (pendukung). Stakeholder sebagai subject adalah Petani, Kelompok tani, Gapoktan, Assosiasi petani jeruk pamelo, Indutri Rumah tangga pengolah jeruk pamelo. Stakeholder sebagai key player, Dinas Tanaman Pangan dan Peternakan, PPL, Pedagang. Stakeholder sebagai context setter Bappeda Kabupaten Pangkep,dan Stakeholder sebagai crowd adalah Camat, Kepala Desa, Perguruan tinggi/lembaga penelitian. Hubungan yang terjadi di antara para stakeholder adalah hubungan kerja sama, hubungan saling mengisi dan hubungan yang berpotensi konflik.